103k views
3 votes
-4x - 2y = 0 -8x – 4y = 0. Solve x and y.

-4x - 2y = 0 -8x – 4y = 0. Solve x and y.-example-1

1 Answer

2 votes

Given:

The equations are,


\begin{gathered} -4x-2y=0\ldots\ldots.(1) \\ -8x-4y=0\ldots\ldots.(2) \end{gathered}

The objective is to solve the value of x and y.

The value of x and y can be calculated using elimination method.

Let's equate the variable x. So multiply equation (1) with 2.


-8x-4y=0\ldots\ldots.(3)

On solving equation (3) and (4),


\begin{gathered} y=0 \\ x=0 \end{gathered}

Hence, the values x and y is zero.

User Marco Rehmer
by
5.6k points